Can evolutionary constraints explain the rarity of nitrogen‐fixing trees in high‐latitude forests?. Issue 4 (13th July 2016) - Menge, Duncan N. L.; Crews, Timothy E.
Summary: The rarity of symbiotic nitrogen (N)‐fixing trees in temperate and boreal ('high‐latitude') forests is curious. One explanation – the evolutionary constraints hypothesis – posits that high‐latitude N‐fixing trees are rare because few have evolved. Here, we consider traits necessary for high‐latitude N‐fixing trees. We then use recent developments in trait evolution to estimate that > 2000 and > 500 species could have evolved from low‐latitude N‐fixing trees and high‐latitude N‐fixing herbs, respectively. Evolution of N‐fixing from nonfixing trees is an unlikely source of diversity. Dispersal limitation seems unlikely to limit high‐latitude N‐fixer diversity. The greater number of N‐fixing species predicted to evolve than currently inhabit high‐latitude forests suggests a greater role for ecological than evolutionary constraints. Contents Summary 1195 I. Introduction 1196 II. The role of diversity 1196 III. An evolutionary framework for the success of high‐latitude N‐fixing woody symbioses 1196 IV. Conclusions 1200 Acknowledgements 1200 References 1200